Environmental Impact and Decomposition of Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Soils: Challenges and Future Directions - Emre, Mehmet; Rubiyatno; Tongco, Jovale Vincent; Permana, Rega (Tropical Aquatic and Soil Pollution, 2024)
The rapid pace of urbanization and development has led to an increasing global concern over polycyclic aromatic hydrocarbons (PAHs) due to their persistent and widespread presence in the environment, posing significant threats to ecosystems and human health. PAHs originate from both natural and human-made sources and can be categorized based on their origin into pyrogenic, petrogenic, and biogenic products. Upon entering the environment, PAHs undergo various chemical and biological transformations, and their movement occurs through processes such as air-to-soil and soil-to-air transport. Composting, a green and cost-effective technology, offers a promising solution for PAH remediation. This process, which includes mesophilic, thermophilic, cooling, and maturing stages, can yield compost that is useful as fertilizer and soil amendment in agriculture. The success of composting depends on factors such as substrate bioavailability, oxygen levels, nutrient supply, and environmental conditions. While composting has shown effectiveness in reducing PAH levels, it is not without challenges, including the risk of weed infestation, greenhouse gas emissions, and odor pollution. The main obstacles in PAH remediation today are the limited bioaccessibility of PAHs and the insufficient focus on the formation of oxygenated PAHs during the process. Future research should address these challenges, particularly by improving PAH bioaccessibility and mitigating issues related to odor and greenhouse gas emissions.